Works on paper of the XIXth and XXth centuries. - Geerinckx, Brigitte; Marquenie, Gilles; Patrick Derom Gallery, Brussel (Brussel : Patrick Derom Gallery, 2002)
Chagall, Marc ; Ensor, James ; Ernst, Max ; Gallait, Louis ; Grosz, George ; Khnopff, Fernand ; Klee, Paul ; Leger, Fernand ; Mammen, Jeanne ; Mellery, Xavier ; Meunier, Constantin ; Miro, Joan ; Modigliani, Amedeo ; Picasso, Pablo ; Rops, Félicien ; Scauflaire, Edgard ; Schwitters, Kurt ; Spilliaert, Léon ; Twombly, Cy ; Wesselman, Tom ; Wiertz, Antoine
Engels
Works on paper of the XIXth and XXth centuries, Patrick Derom Gallery, Brussel / New York, Spring 2002
boek
Keywords: 19de eeuw; 20ste eeuw